Sublimasi Kekerasan dalam Agama - Haqqul Yaqin (HUMANISTIKA : Jurnal Keislaman, 2017)
The negative role of religion will create a peace recognized as we can not deny that. One of the content of the confession: 1) the practice of our religious communities sometimes in the world are divisive forces. 2) too often we are more attuned to the powers of the world, also if they make a mistake, instead of opposing that power on the basis of the teachings of our religions. 3) We do not quite apply as servants and defenders of suffering and we exploit mankind. 4) Too little we seek to build mutual understanding and interfaith fellowship at the local level, from which strong prejudices arise. Answering efforts and the ability to respond to these challenges will further demonstrate the role and role of religion in the form of social relationships that mature. If this fact happens, then the desire to make religion as an ethical foundation in overcoming violence is not a utopia. Religion is no longer an empty wish that always conceals its good intentions and always appreciates the political ambition of its adherents, but religion with a constantly awakened and awakened distinction is social coherence and harmony.